3D numerical study of hydrogen storage in nano-enhanced metal hydride reactor with branching type fins - Selimefendigil, Fatih; Senol, Gurel; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2026)
In this paper, 3D numerical study of hydrogen storage in a metal hydride (MH) reactor is examined by installing branching type fins and nano-enhanced MH. Titanium dioxide (TiO2) is utilized as the nanomaterial to be used as an additive in the MH domain in terms of heat transfer enhancement during the absorption. The metal hydride used for the reactor is MgH2 due its high volumetric and gravimetric capacity. Comparative studies are performed for the hydrogen storage system by using finite element-based solver. Number of branching fins used during the absorption is taken between 10and 50 while hydrogen supply pressure is considered between 5and 15atm. The coolant temperature is considered between 5 degrees C and 20 degrees C. Percentage weight (wt%) of absorbed hydrogen, and average MH bed temperatures are evaluated for each case and comparative results are presented. The best case is obtained with 50 branching fins, at supply pressure as 15atm and the coolant temperature as 5 degrees C. Using 50 fins results in reduction of sorption time by 22 % and the average bed temperature in the MH bed by 27 %. The coolant temperature at 5 degrees C reduces the absorption time and the average bed temperature by 34 % and 48 %, respectively, while the highest-pressure case results in a 48 % reduction in the sorption time compared to the lowest pressure case. Results are useful for the design and development of thermal management systems for hydrogen storage in MH reactors.
Keywords: Metal hydride; Hydrogen storage; Branching fin; Nano enhanced